A method for preparing type A molecular sieve
The method for preparing type A molecular sieves by spray roasting a mixture of natural minerals and dispersants followed by acid treatment, combined with organic polymer treatment, solves the problems of complex synthesis process and high cost of type A molecular sieves, realizes efficient and low-cost molecular sieve preparation, and improves the application efficiency and quality of molecular sieves.
Patent Information
- Application Number
- CN202210550487.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-05-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-05-18
AI Technical Summary
Existing A-type molecular sieve synthesis processes are complex, costly, and have low single-reactor yields. Furthermore, they present separation difficulties during application, making it difficult to meet industrial demands.
Natural minerals and dispersants are mixed and sprayed into microspheres, which are then calcined, acid-treated, and then molecular sieve structural units treated with organic polymers are added. The mixture is then reacted with sodium hydroxide solution in a crystallization reactor. The synthesis ratio and temperature are controlled to form a highly efficient type A molecular sieve.
It significantly improves the synthesis efficiency and product quality of type A molecular sieves, reduces production costs, simplifies the process flow, and increases single-batch yield and crystallization speed.
Smart Images

Figure 00000000_0000_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of molecular sieve preparation, and specifically relates to a method for preparing type A molecular sieve. Background Art
[0002] Type A molecular sieves have been used in traditional applications such as drying, refining, and adsorption separation due to their rich pore structure, high specific surface area, and high ion exchange capacity. In recent years, their applications in membrane separation, host-guest material assembly, and antibacterial material carriers have attracted increasing attention. The main component of type A molecular sieves is aluminosilicate, and its structure is similar to the crystal structure of sodium chloride. Sodium chloride crystals are composed of sodium ions and chloride ions. If all the sodium ions and chloride ions in the sodium chloride lattice are replaced with β cages, and two adjacent β cages are connected to each other through four-membered rings with four oxygen bridges, the crystal structure of type A molecular sieves is obtained. The pore size is It is called 4A (also known as sodium A type) molecular sieve, using Ca 2+ Exchange Na in 4A molecular sieve + ,form The pore size is 5A (also known as calcium A type) molecular sieve, and K + Na exchange of 4A molecular sieve + ,form The pore size is 3A (also known as potassium A type) molecular sieve. Among them, the most widely used are 4A and 5A molecular sieves.
[0003] Type A molecular sieves are widely used in adsorption separation, moisture absorption, magnetic separation, etc. In order to improve the separation and moisture absorption of molecular sieves, the research and development trend tends to small grains, multi-level pores, high silicon-aluminum ratio, etc. However, the currently publicly reported synthesis process steps of type A molecular sieves are complicated and not conducive to industrial implementation; some patents introduce a large amount of organic templates in the synthesis method, which is not environmentally friendly; more patents use chemical synthesis raw materials for preparation, and the single-pot yield is low and the cost is high; some patents disclose a method for preparing molecular sieves based on kaolin thermal phase change and alkaline treatment to obtain silicon-aluminum sources, but there is no detailed introduction on how to solve the separation difficulties of the prepared molecular sieves during the application process. With the rapid development of adsorption and separation in fine chemicals, type A molecular sieves, as a kind of aluminosilicate molecular sieves, its synthesis is the same as other molecular sieves. It should try to seek a low-cost, economical and efficient synthesis route to solve the problems of cost, performance, separation, etc., broaden the application range of type A molecular sieves, and improve their application efficiency and quality. Summary of the invention
[0004] In view of the defects of the above-mentioned technology, the purpose of the present invention is to provide a preparation method for type A molecular sieve with low cost, high efficiency and high single-pot yield, which can significantly improve product quality and efficiency while reducing production costs.
[0005] The method for preparing type A molecular sieve adopted in the present invention comprises the following steps:
[0006] (1) natural minerals are mixed with a dispersant and deionized water to obtain a slurry having a solid content of 20-55%, the slurry is sprayed into microspheres having a median diameter of 150-180 μm, the microspheres are calcined at 600-1000° C., and the calcined microspheres are treated with an acid to obtain a mixture A;
[0007] (2) adding the molecular sieve structural unit to an organic polymer for treatment to obtain a mixture B, wherein the treatment conditions are 50-120° C. and 0.5-6 h;
[0008] (3) Add mixture B and sodium hydroxide solution to mixture A in sequence, put into a crystallization reactor, crystallize at 50-100° C. for 2-12 hours, filter to remove the mother liquor, and dry the solid material to obtain a high-purity type A molecular sieve.
[0009] A low-cost, high-efficiency, high-yield single-pot A-type molecular sieve preparation method significantly improves product quality and efficiency while reducing production costs.
[0010] In the preparation method of the present invention, in step (1), the preferred conditions for the acid treatment include: the acid is an inorganic acid and / or an organic acid, the inorganic acid is selected from one or more of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, and the organic acid is selected from one or more of formic acid, citric acid, oxalic acid, and acetic acid. The concentration of the acid solution used is 0.01-15 mol / L, the liquid-to-solid mass ratio is 4-15, the temperature is 20-100° C., the pH value is 2.8-6.0, and the treatment time is 10-100 minutes.
[0011] The sprayed and calcined microspheres are first treated with acid to obtain extensive pores inside the microspheres, which significantly increases the specific surface area of the microspheres, allowing the microspheres to better contact with the reactants, thereby improving the speed and efficiency of the reaction.
[0012] In the preparation method of the present invention, in step (1), the natural mineral preferably includes one of kaolin, coal gangue, montmorillonite, halloysite, attapulgite and bentonite, and the median diameter is 0.5-5 μm.
[0013] The above natural minerals are selected to provide the silicon source required for synthesis on the one hand, and to provide a pore-rich carrier for the growth of molecular sieve sites after acid treatment on the other hand.
[0014] In the preparation method of the present invention, in step (2), the composition ratio of the molecular sieve structural unit preferably satisfies SiO2:Al2O3:Na2O=40-80:1-20:10-40 (mass ratio).
[0015] In the preparation method described in the present invention, in step (3), the synthesis ratio of sodium hydroxide solution, sodium silicate, molecular sieve structural unit and deionized water after addition is preferably: Na2O / Al2O3=2-5, SiO2:Al2O3=1.5-3.0, H2O / Al2O3=80-200, soil ball / liquid phase=0.05-0.6 (mass ratio).
[0016] In the preparation method of the present invention, in step (2), the molecular sieve structural unit can come from the mother liquor formed in the synthesis of NaY by the gel method or the silica-alumina gel formed by the reaction of the mother liquor and aluminum sulfate; it can also be the mother liquor generated during the in-situ crystallization process or the silica-alumina gel formed by the reaction of the mother liquor and aluminum sulfate; it can also be a composition formed by directly mixing sodium silicate and sodium aluminate and aging them at 90°C for 3-5 hours.
[0017] The molecular sieve structural units selected above all come from the crystallization system, which can improve the utilization rate of raw materials in the crystallization process and realize zero-emission production of the device.
[0018] In the preparation method of the present invention, in step (2), the treatment conditions are preferably 60-100° C. and 1-4 h.
[0019] The appropriate treatment temperature can accelerate the expansion and extension of polymer side chains, thereby better mixing with the molecular sieve structural units, accelerating the reaction speed and improving the reaction efficiency.
[0020] In the preparation method of the present invention, in step (3), the amount of the structural unit added is preferably 10-50% of the mass of the microspheres.
[0021] After the molecular sieve structural unit is obtained, adding organic polymers for treatment during the crystallization process can play a partial role as silicon, aluminum and sodium sources, allowing the side chains of the polymer to be unfolded and extended, shortening the generation time of the silicon-aluminum structural unit required for molecular sieve synthesis and accelerating the induction and crystallization process.
[0022] In the preparation method of the present invention, in step (2), the organic polymer is preferably carboxymethyl cellulose, methyl cellulose or one of cellulose and starch, and the added amount is preferably 1-20% of the mass of the molecular sieve structural unit.
[0023] The organic polymer can accommodate the molecular sieve after subsequent treatment. A reasonable addition range can not only provide sites for the growth of the molecular sieve, but also ensure the maximum reaction.
[0024] In the preparation method of the present invention, in step (1), the dispersant preferably includes one of sodium silicate, sodium pyrophosphate, silica sol, aluminum sol, sodium hydroxide, and sodium hexametaphosphate, and the added amount is preferably 1-20% of the amount of the natural mineral, preferably 2-15%.
[0025] The addition of an appropriate amount of dispersant can evenly disperse inorganic and organic solid and liquid particles that are difficult to dissolve in liquids, and can also prevent the sedimentation and agglomeration of particles, thus better promoting the reaction.
[0026] Beneficial effects of the present invention:
[0027] The preparation method disclosed in the present invention firstly treats the sprayed and calcined microspheres with acid, and then adds the molecular sieve structural units treated with organic polymers, which can significantly improve the synthesis efficiency while reducing the synthesis cost, and has the advantages of short crystallization time, stable product quality, simple process, high single-pot yield, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 Phase diagram of type A molecular sieve prepared in Example 1-3
[0029] Figure 2 Phase diagram of type A molecular sieve prepared in Example 4-10
[0030] Figure 3 This is the SEM image of the type A molecular sieve prepared in Example 1 DETAILED DESCRIPTION
[0031] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.
[0032] The test methods described in the following examples are conventional methods unless otherwise specified; the reagents and compounds described are commercially available unless otherwise specified.
[0033] Source of raw materials: natural minerals, industrial products, sodium silicate (SiO2: 19.75%, Na2O: 6.95%, H2O: 73.30%), industrial products, high-alkali sodium aluminate (Al2O3: 3.17%, Na2O: 21.12%), industrial products, directing agent (16SiO2: 0.8Al2O3: 15.7Na2O: 312H2O), industrial agent, aluminum sol (Al2O3: 21.22%) , industrial products, all collected from the catalyst plant of Lanzhou Petrochemical Company; carboxymethyl cellulose, analytical grade, 100g, methyl cellulose, analytical grade, 100g, starch, analytical grade, 100g (Shanghai test); NaOH, analytical grade, Longyao Group; alkaline silica sol (SiO2: 30%), industrial product, Yantai Hengxin Chemical Technology Co., Ltd.; sodium pyrophosphate, analytical grade, Tianjin Komio Chemical Reagent Co., Ltd.; hydrochloric acid, chemically pure; ammonia water, chemically pure.
[0034] Analytical methods:
[0035] The crystallinity of the molecular sieve was tested by using a D / max-3C X-ray powder diffractometer produced by Rigaku, Japan; the crystallinity of the sample was determined by X-ray diffraction. The pore distribution of the sample was tested by using an Autosorb-3B specific surface measuring instrument produced by Quantachrome, USA; the specific surface area, pore size distribution and pore volume of the sample were determined by a N2 low temperature (77.3K) adsorption-desorption experimental method.
[0036] Embodiment 1:
[0037] 1500g of kaolin was mixed with 300g of sodium hexametaphosphate and deionized water to make a slurry with a solid content of 50%. The mixed slurry was then sprayed into microspheres with a median diameter of 180μm, and then calcined at 1000℃ for 20min. 500g of the calcined soil balls were added to a 15mol / L nitric acid solution with a liquid-to-solid ratio of 15, treated at 60℃ for 100min, and the pH value was controlled at 2.8 to obtain A. 100g of Y-type molecular sieve mother liquor was weighed as a molecular sieve structural unit (SiO2: Al2O3: Na2O = 79.8: 20: 39.6) and mixed with 20g of carboxymethyl cellulose, and treated at 50℃ for 6h to obtain B. A1 and B1 were mixed and then 1300g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3 = 2.1, SiO2 / Al2O3 = 3.0, and H2O / Al2O3 = 200. The material was stirred for 2 hours and then put into a crystallization reactor for crystallization at 100° C. for 12 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J1.
[0038] Embodiment 2:
[0039] 2000g of halloysite was mixed with 20g of sodium hydroxide and deionized water to make a slurry with a solid content of 40%. The mixed slurry was then sprayed into microspheres with a median diameter of 170μm, and then calcined at 700℃ for 40min. 1000g of the calcined soil balls were added to a 3mol / L sulfuric acid solution with a liquid-to-solid ratio of 7 and treated at 80℃ for 20min. The pH value was controlled at 3.5 to obtain A2. 200g of the silica-alumina gel (SiO2:Al2O3:Na2O=52:14:23) formed by the reaction of NaY mother liquor from the gel method with aluminum sulfate was weighed as a molecular sieve structural unit and mixed with 2g of starch, and treated at 120℃ for 0.5h to obtain B2. After A2 and B2 were mixed, 2800g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3=3.3, SiO2 / Al2O3=2.6, and H2O / Al2O3=150. After stirring the material for 2 hours, it was put into a crystallization reactor and crystallized at 97°C for 10 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J2.
[0040] Embodiment 3:
[0041] 700g of montmorillonite was mixed with 119g of sodium pyrophosphate and deionized water to make a slurry with a solid content of 30%. The mixed slurry was then sprayed into microspheres with a median diameter of 150μm, and then calcined at 960℃ for 100min. 500g of the calcined soil balls were added to a 12mol / L hydrochloric acid solution with a liquid-to-solid ratio of 4, treated at 40℃ for 80min, and the pH value was controlled at 3.0 to obtain A3. 150g of the molecular sieve structural unit (SiO2:Al2O3:Na2O=75:3:21) from the in-situ crystallization mother liquor was weighed as a molecular sieve structural unit and treated with 6g of cellulose at 100℃ for 4h to obtain B3. After A3 and B3 were mixed, 1200g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3=4.5, SiO2 / Al2O3=2.8, and H2O / Al2O3=130. After stirring the material for 2 hours, it was put into a crystallization reactor and crystallized at 55°C for 8 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J3.
[0042] Embodiment 4:
[0043] 600g of attapulgite was mixed with 60g of silica sol and deionized water to make a slurry with a solid content of 20%. The mixed slurry was then sprayed into microspheres with a median diameter of 160μm, and then calcined at 600℃ for 120min. 400g of the calcined soil balls were added to a 2mol / L acetic acid solution with a liquid-to-solid ratio of 5.5, treated at 90℃ for 90min, and the pH value was controlled at 4.5 to obtain A4. 200g of the structural unit (SiO2:Al2O3:Na2O=67:15:16) from the reaction of the in-situ crystallization mother liquor with aluminum sulfate was weighed and treated with 32g of methyl cellulose at 80℃ for 2h to obtain B4. A4 and B4 were mixed and then 800g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3=2.7, SiO2 / Al2O3=1.5, and H2O / Al2O3=185. After stirring the material for 2 hours, it was put into a crystallization reactor and crystallized at 77°C for 10 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J4.
[0044] Embodiment 5:
[0045] 900g bentonite was mixed with 45g aluminum sol and deionized water to make a slurry with a solid content of 27%. The mixed slurry was then sprayed into microspheres with a median diameter of 175μm, and then calcined at 870℃ for 80min. 667g of the calcined soil balls were added to 7mol / L phosphoric acid solution with a liquid-to-solid ratio of 10, treated at 70℃ for 70min, and the pH value was controlled at 5.1 to obtain A5. 150g of the molecular sieve structural unit (SiO2:Al2O3:Na2O=66:16:11) from sodium silicate and sodium metaaluminate aged for 3 hours was weighed and treated with 9g of carboxymethyl cellulose at 70℃ for 5h to obtain B5. A5 and B5 were mixed and then 1100g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3=3.5, SiO2 / Al2O3=1.9, and H2O / Al2O3=80. After stirring the material for 2 hours, it was put into a crystallization reactor and crystallized at 86° C. for 4 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J5.
[0046] Embodiment 6:
[0047] 1500g of palygorskite was mixed with 120g of sodium hydroxide and deionized water to make a slurry with a solid content of 25%, and then the mixed slurry was sprayed into microspheres with a median diameter of 150μm, and then calcined at 930℃ for 110min. 400g of the calcined soil balls were added to 0.1mol / L formic acid solution, with a liquid-to-solid ratio of 13, treated at 50℃ for 100min, and the pH value was controlled at 5.8 to obtain A6. 100g of the molecular sieve structural unit (SiO2:Al2O3:Na2O=73:3.5:20) from the in-situ crystallization mother liquor was weighed and treated with 12g of starch at 90℃ for 4.5h to obtain B6. After A6 and B6 are mixed, 3000g of sodium hydroxide solution is added to ensure that the synthetic ratio is Na2O / Al2O3=3.8, SiO2 / Al2O3=2.2, H2O / Al2O3=95, soil ball / liquid phase=0.43. After stirring the materials for 2h, they are put into the crystallization reactor, crystallized at 62℃ for 6h, the mother liquor is removed by filtration, and the solid material is dried to obtain type A molecular sieve J6.
[0048] Embodiment 7:
[0049] 1000g of sepiolite was mixed with 30g of sodium hydroxide and deionized water to make a slurry with a solid content of 38%. The mixed slurry was then sprayed into microspheres with a median diameter of 165μm, and then calcined at 780℃ for 60min. 857g of the calcined soil balls were added to a 1.5mol / L oxalic acid solution with a liquid-to-solid ratio of 9, treated at 30℃ for 60min, and the pH value was controlled at 4.0 to obtain A7. 300g of the molecular sieve structural unit (SiO2:Al2O3:Na2O=62:4.8:31) from the NaY mother liquor was weighed and treated with 9g of cellulose at 80℃ for 3.6h to obtain B7. After A7 and B7 were mixed, 1600g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3=4.2, SiO2 / Al2O3, and H2O / Al2O3=110. After stirring the material for 2 hours, it was put into a crystallization reactor and crystallized at 98°C for 12 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J7.
[0050] Embodiment 8:
[0051] 600g of kaolinite was mixed with 72g of silica sol and deionized water to make a slurry with a solid content of 42%. The mixed slurry was then sprayed into microspheres with a median diameter of 155μm, and then calcined at 800℃ for 120min. 445g of the calcined soil balls were added to a 0.6mol / L citric acid solution with a liquid-to-solid ratio of 11, treated at 90℃ for 40min, and the pH value was controlled at 4.3 to obtain A8. 200g of molecular sieve structural units (SiO2:Al2O3:Na2O=52:15:22) formed by the reaction of NaY mother liquor from the gel method with aluminum sulfate and treated with 34g of methyl cellulose at 60℃ for 5.5h to obtain B8. A8 and B8 were mixed and then 990g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3=2.4, SiO2 / Al2O3=1.6, and H2O / Al2O3=160. After stirring the material for 2 hours, it was put into a crystallization reactor and crystallized at 75°C for 9 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J8.
[0052] Embodiment 9:
[0053] 3000g bentonite was mixed with 480g sodium pyrophosphate and deionized water to make a slurry with a solid content of 47%. The mixed slurry was then sprayed into microspheres with a median diameter of 180μm, and then calcined at 650℃ for 50min. 2500g of the calcined soil balls were added to a 4mol / L nitric acid solution with a liquid-to-solid ratio of 8, treated at 50℃ for 90min, and the pH value was controlled at 3.7 to obtain A9. 300g of the molecular sieve structural unit (SiO2:Al2O3:Na2O=76:2:25) from the in-situ crystallization mother liquor was weighed and treated with 24g starch at 100℃ for 5h to obtain B9. After A9 and B9 were mixed, 3000g of sodium hydroxide solution was added to ensure that the synthetic ratios were Na2O / Al2O3=2.9, SiO2 / Al2O3=1.8, and H2O / Al2O3=140. After stirring the material for 2 hours, it was put into a crystallization reactor and crystallized at 83°C for 7 hours. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J9.
[0054] Example 10
[0055] 1000g of attapulgite was mixed with 130g of aluminum sol and deionized water to make a slurry with a solid content of 55%, and then the mixed slurry was sprayed into microspheres with a median diameter of 150μm, and then calcined at 830℃ for 90min. 606g of the calcined soil balls were added to 9mol / L phosphoric acid solution with a liquid-solid ratio of 6, treated at 100℃ for 10min, and the pH value was controlled at 2.8 to obtain A10. 200g of the molecular sieve structural unit (SiO2:Al2O3:Na2O=65:14:16) of the silica-alumina colloid obtained from the reaction of the in-situ crystallization mother liquor with aluminum sulfate was weighed and treated with 20g of cellulose carboxymethyl cellulose at 70℃ for 1h to obtain B10. After A10 and B10 were mixed, 2300g of sodium hydroxide solution was added to ensure that the synthetic ratio was Na2O / Al2O3=4.8, SiO2 / Al2O3=2.9, H2O / Al2O3=100. After stirring for 2h, the materials were put into a crystallization reactor and crystallized at 50°C for 7h. The mother liquor was filtered out and the solid material was dried to obtain type A molecular sieve J10.
[0056] Comparative Example:
[0057] The difference from Example 9 is that the calcined microspheres are not treated with acid, and no molecular sieve structural units treated with organic polymers are added.
[0058] 3000g bentonite was mixed with 480g sodium pyrophosphate and deionized water to make a slurry with a solid content of 47%. The mixed slurry was then sprayed into microspheres with a median diameter of 180μm, and then calcined at 650℃ for 50min. 2500g of the calcined soil balls were added with 3000g of sodium hydroxide solution to ensure that the synthetic ratio was Na2O / Al2O3=2.9, SiO2 / Al2O3=1.8, and H2O / Al2O3=140. After stirring the material for 2h, it was put into a crystallization reactor, crystallized at 83℃ for 7h, the mother liquor was removed by filtration, and the solid material was dried to obtain type A molecular sieve J11.
[0059] Table 1 lists the structures and physical parameters of the molecular sieves synthesized in Examples 1-8 and Comparative Examples.
[0060] Table 1
[0061]
[0062]
[0063] It can be seen from Table 1 that the crystallinity, specific surface area and total pore volume of the samples obtained by the embodiment of the preparation method of the present invention are improved. In the crystallization process, the molecular sieve structural unit treated with an organic polymer is used as a partial silicon, aluminum and sodium source in the synthesis. This method allows the side chains of the polymer to be unfolded and extended. After mixing with the molecular sieve structural unit, many "silicon cage" environments suitable for the growth of molecular sieves can be formed, which ensures the growth points of the molecular sieve, shortens the generation time of the silicon aluminum structural unit required for the molecular sieve synthesis, and further shortens the crystallization time; at the same time, the molecular sieve structural unit also has a certain crystallization guiding effect, improves the crystallization quality, and reduces the production cost.
[0064] In summary, the sprayed and calcined microspheres are first treated with acid, and then the molecular sieve structural units treated with organic polymers are added. This can significantly improve the synthesis efficiency while reducing the synthesis cost. It has the advantages of short crystallization time, stable product quality, simple process, and high single-pot yield.
[0065] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the present invention.
Claims
1. A method for preparing type A molecular sieve, characterized in that: The following steps are involved: (1) Natural minerals are mixed with a dispersant and deionized water to obtain a slurry having a solid content of 20-55%. The mixed slurry is sprayed into microspheres having a median diameter of 150-180 μm, and the microspheres are calcined at 600-1000° C. The calcined microspheres are treated with an acid to obtain a mixture A; (2) adding an organic polymer to the molecular sieve structural unit for treatment to obtain a mixture B, wherein the treatment conditions are 50-120° C. and 0.5-6 h; (3) Add mixture B and sodium hydroxide solution to mixture A in sequence, put into a crystallization reactor, crystallize at 50-100°C for 2-12 hours, filter to remove the mother liquor, and dry the solid material to obtain high-purity type A molecular sieve; In step (2), the molecular sieve structural unit composition ratio should satisfy SiO2:Al2O3:Na2O=40-80:1-20:10-40 in terms of mass ratio.
2. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (1), the acid treatment conditions include: the acid is an inorganic acid and / or an organic acid, the inorganic acid is selected from one or more of sulfuric acid, hydrochloric acid, nitric acid, and phosphoric acid, and the organic acid is selected from one or more of formic acid, citric acid, oxalic acid, and acetic acid. The acid solution used has a concentration of 0.01-15 mol / L, a liquid-to-solid mass ratio of 4-15, a temperature of 20-100° C., a pH value of 2.8-6.0, and a treatment time of 10-100 minutes.
3. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (1), the natural mineral includes one of kaolin, coal gangue, montmorillonite, halloysite, attapulgite and bentonite, and has a median diameter of 0.5-5 μm.
4. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (3), after the sodium hydroxide solution, sodium silicate, molecular sieve structural unit and deionized water are added, the synthetic mass ratio is: Na2O / Al2O3=2-5, SiO2 / Al2O3=1.5-3.0, H2O / Al2O3=80-200, soil ball / liquid phase=0.05-0.
6.
5. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (2), the molecular sieve structural unit is derived from the mother liquor formed in the synthesis of NaY by the gel method or the silica-alumina gel formed by the reaction of the mother liquor with aluminum sulfate; or the mother liquor generated during the in-situ crystallization process or the silica-alumina gel formed by the reaction of the mother liquor with aluminum sulfate; or the composite formed by directly mixing sodium silicate and sodium metaaluminate and aging them at 90°C for 3-5 hours.
6. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (2), the treatment conditions are 60-100° C. and 1-4 h.
7. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (3), the amount of the structural unit added accounts for 10-50% of the mass of the microspheres.
8. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (2), the organic polymer is carboxymethyl cellulose, methyl cellulose or one of cellulose and starch, and the added amount is 1-20% of the mass of the molecular sieve structural unit.
9. The method for preparing type A molecular sieve according to claim 1, characterized in that: In step (1), the dispersant includes one of sodium silicate, sodium pyrophosphate, silica sol, aluminum sol, sodium hydroxide, and sodium hexametaphosphate, and the added amount is 1-20% of the amount of the natural mineral.
10. The method for preparing type A molecular sieve according to claim 9, characterized in that: In step (1), the amount of the dispersant added is 2-15% of the amount of the natural mineral.
Citation Information
Patent Citations
Porous composite material containing NaA zeolite molecular sieve and preparation method thereof
CN104261424A
Preparation method of nano type A molecular sieve
CN110498423A